Meaningful work and organizational citizenship behavior among lecturers: The mediating role of work passion - Endro Puspo Wiroko (Universitas Negeri Padang, 2021)
The previous meta-analysis found that the corrected correlation between meaningful work and organizational citizenship behavior was relatively low.This study investigates the mediating effect of work passion in the relationship between meaningful work and organizational citizenship behavior. Data were collected using an online self-report questionnaire on full-time lecturers in some cities in Indonesia (N=162). Data were analyzed using Hayes PROCESS macro on SPSS software. Results showed that meaningful work was positively related to organizational citizenship behavior and work passion. Results also showed that work passion was positively correlated with organizational citizenship behavior. The mediation analysis showed that work passion fully mediated the relationship between meaningful work and organizational citizenship behavior. The theoretical and practical implications of the study were further discussed.